INDIGENOUS PUBLIC MANAGEMENT IN BRAZIL: CONSIDERATIONS ON THE APPOINTMENT OF TRUST POSITIONS AND TERRITORIAL POLICIES - Baggio Di Sopra, Fernando Ernesto; Tupari de Araujo, Rosane Taynara; da Silva Gonçalves, Euliene (Revista Gênero e Interdisciplinaridade, 2023)
This article addresses aspects related to indigenous public management in Brazil, from the perspective of the ethics of understanding, theorized by Edgar Morin. Assuming that many indigenous communities have not yet been guaranteed possession of their ancestral territories, in line with the provisions of Article 231 of the Federal Constitution, this academic work aims to identify factors that may be impacting the effective guarantee of the territorial rights of native peoples. As a methodological parameter for quantitative analysis, it was decided to systematize data referring to the demarcation of indigenous lands in each government after the 1985 re-democratization. freely appointed positions within the scope of the National Foundation for Indigenous Peoples (Funai). Considering that all the recent presidents of Brazil made political concessions to the agribusiness caucus in the Federal Congress with the aim of making governability viable, it can be concluded that none of the last indigenous public administrations acted effectively in the sense of proceeding with the fulfillment of the territorial demands of the indigenous peoples, as such a measure is directly opposed to the interests of the congressional agribusiness group. Considering that ethics is configured as one of the fundamental pillars on which public management is based, this article sought to identify possible uses of private objectives, alien to the foundations of state indigenism, in the appointment of Funai leaders, who tend to overlap their particular interests to the public function of the indigenist agency.